Lean Hypotheses and Effectual Commitments: An Integrative Framework Delineating the Methods of Science and Entrepreneurship - Sarasvathy, Saras D. (Journal of Management, 2024)
Recently, there is increasing interest in building theories that offer actionable guidance to the practice of entrepreneurship. Here I present a general theoretical framework, called CAVE, for understanding, assessing, and enhancing existing tools that offer such guidance. The framework encompasses a two-dimensional space with prediction and control as its axes. The CAVE framework accommodates a wide variety of extant practical tools as well as relevant concepts from psychology and economics. Specifically, I compare and contrast effectuation with lean startup within this framework. Whereas lean startup centers around hypothesis testing, effectuation focuses on cocreative commitments from self-selecting stakeholders. In other words, the former takes markets as exogenous, while the latter explicates how they can be made endogenous and why that matters. More generally, I show how these differences connect with and delineate the scientific method from the entrepreneurial method.